Respiratory measures in amyotrophic lateral sclerosis. Issue 5 (3rd July 2018) - Lechtzin, Noah; Cudkowicz, Merit E.; de Carvalho, Mamede; Genge, Angela; Hardiman, Orla; Mitsumoto, Hiroshi; Mora, Jesus S.; Shefner, Jeremy; Van den Berg, Leonard H.; Andrews, Jinsy A.
Abstract: Objective : Amyotrophic lateral sclerosis (ALS) is a progressive neuromuscular disease that causes skeletal muscle weakness, including muscles involved with respiration. Death often results from respiratory failure within 3–5 years. Monitoring respiratory status is therefore critical to ALS management, as respiratory/pulmonary function tests (PFTs) are used to make decisions including when to initiate noninvasive ventilation. Understanding the different respiratory and PFTs as they relate to disease progression and survival may help determine which tests are most suitable. Methods : This review describes the tests used to assess respiratory muscle and pulmonary function in patients with ALS and the correlations between different respiratory measures and clinical outcomes measures. Results : The most commonly used measurement, forced vital capacity (VC), has been shown to correlate with clinical milestones including survival, but also requires good motor coordination and facial strength to form a tight seal around a mouthpiece. Other tests such as slow VC, sniff inspiratory pressure, or transdiaphragmatic pressure with magnetic stimulation are also associated with distinct advantages and disadvantages. Conclusions : Therefore, how and when to use different tests remains unclear. Understanding how each test relates to disease progression and survival may help determine which is best suited for specific clinical decisions.